Mavericks of sound : conversations with artists who shaped indie and roots music - Ensminger, David A. (Published by Rowman & Littlefield, 2014)
In this book, music scholar David Ensminger offers a collection of compelling interviews with legendary roots rock and indie artists who bucked mainstream trends and have remained resilient in the face of enormous shifts in the music world. Ensminger brings to light the highways and byways trod by these music icons over the course of their careers.